The Concept of Autonomy and the Changing Character of War - John O Birkeland (Oslo Law Review)
There has been an immense development in unmanned aircraft technology in the past three decades or so. The percentage of unmanned versus manned aircraft in combat operations is only predicted to grow in the future. The public’s aversion to risk and the endurance facilitated by modern unmanned systems have both played important roles in the growth of unmanned aircraft in modern warfare. Increasingly complex warfare scenarios call for increasingly complex weapons systems, and autonomous aircraft are predicted to play a crucial role in meeting tomorrow’s operational challenges. The article argues that even though autonomous systems will be able to make tactical decisions by themselves, these decisions will not be acted upon in a vacuum – even autonomous machines will be a part of the military and political chain-of-command. Operational concepts such as ‘loyal wingman’, Manned-Unmanned Teaming, motherships and swarming are the beginning of a new autonomous way of warfare. It is important that we tailor our autonomous machines to operate inside the realm of military and political control. It is thus crucial to have a broad debate among policy makers, technology developers, scholars and civil society in order to decide how the weapons of the future will be programmed and the place and scope that human control should play therein.